Enucleation Induces Parvalbumin and Glial Fibrillary Acidic Protein, but Not Calbindin D28k Protein Expression in Superior Colliculus of Wistar Rats - Daniel Gonzalez; Szeifoul Afadlal; Kristin Lizal; Yulius Hermanto; Takanori Miki; Yoshiki Takeuchi; Irawan Satriotomo (Molecular and Cellular Biomedical Sciences, 2018)
Background: It is known that eye enucleation causes various morphological and functional alterations in the central nervous system (CNS). The purpose of this study was to examine the sub-chronic effects of monocular enucleation on the distribution of the calcium binding proteins calbindin D28k (CB) and parvalbumin (PV) as well as the glial fibrillary acidic protein (GFAP) immunoreactivity in the superior colliculus (SC) of Wistar rats.Materials and Methods: Thirty young adult (8 weeks) male Wistar rats from SLC (Shizuoka, Japan), weighing 200-250 grams, were housed in separate cages under controlled conditions with a constant temperature kept in 12:12 light/dark cycle and ad libitum water and food. In this study the rats were divided into two groups, a control and an enucleated groups. The experimental group received unilateral eye enucleation and was allowed 1, 4 or 12 weeks recovery before sacrificed.Results: Unilateral enucleation over a period of 1 week or more caused a decrease in the number CB-immunoreactive (CBIR) neurons. This loss was associated with an increase in GFAP-IR astrocytes in the superficial gray layer and the optic layer of the SC with contralateral side predominance. In addition, the CB-IR neurons illustrated a smaller soma and poor dendritic arborization. Conversely, the GFAP-IR astrocytes were hypertrophied with longer foot processes on the contralateral side of enucleation. Interestingly, the number of PV-IR neurons was elevated for up to 4 weeks in enucleated rats versus shamoperated rats.Conclusion: This study demonstrates the importance of calcium-binding protein homeostasis and reversible glial response for maintaining variability of neuronal function in sub-cortical visual centers following optic nerve deafferentation.Keywords: enucleation, superior colliculus, calbindin D28k, parvalbumin, glial fibrillary acidic protein